Fabrication of Al-matrix composite reinforced with quasicrystals using conventional metallurgical fabrication methods. (December 2019) - Wolf, Witor; Bolfarini, Claudemiro; Kiminami, Claudio S.; Botta, Walter J.
Abstract: Al-matrix composites reinforced with quasicrystals are mostly fabricated by methods that apply rapid solidification techniques or by means of powder metallurgy. In this work, we show a metallic system that forms such microstructure containing the quasicrystalline, Al7 Cu2 Fe and aluminum phases by casting an appropriate composition followed by a thermal treatment. An Al85 Cu6.75 Fe3.375 Cr4.875 (%at.) alloy was arc-melted, annealed and subsequently characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. We show that it is possible to fabricate Al-matrix composites reinforced with quasicrystals using conventional metallurgical processes. This opens new perspectives for application of quasicrystalline alloys and composites. Graphical abstract: Unlabelled Image